Morbidade hospitalar em município da região Sul do Brasil em 1992 Hospital morbidity in an urban area of Southern Brazil, in 1992 - Thais A. F. Mathias; Maria Lúcia de M. S. Soboll (Revista de Saúde Pública, 1996)
Com o objetivo de caracterizar a morbidade hospitalar, foi analisada uma amostra constituída por 2.518 internacões de 8 hospitais gerais do Município de Maringá-PR, Brasil, em 1992, segundo as variáveis: diagnóstico, sexo, idade, procedência, fonte de financiamento, tempo de permanência e tipo de saída. Os diagnósticos mais importantes foram: as complicacões da gravidez, parto e puerpério, doenças do aparelho respiratório e doenças do aparelho circulatório. Das internacões, 42,8% foram para pacientes do sexo masculino e, quando ajustadas por ano de idade, se concentraram em crianças de até 4 anos. A maior parte das internações foi financiada pelo Sistema Único de Saúde (SUS) (73,8%) e pelos pacientes procedentes do Município de Maringá (66,4%). A duração média da internação foi de 3,6 dias e o coeficiente de mortalidade hospitalar de 2,7 óbitos em cada 100 internações. The distribution of the 2,518 admissions obtained in a sample taken from all the admissions which occurred in the eight general hospitals of the city of Maringá, State of Paraná, Brazil, in 1992 was analysed. The study variables were: main diagnosis, sex, age, city of residence, souces of financing, length of stay and discharge type. The leading causes of hospitalization were (ICD-9): complications of pregnancy, childbirth and puerperium and diseases of the respiratory and circulatory systems. Of the admissions, 42.8% were of men and when age adjusted, the highest proportion was found to be of children below 4 years of age. In the study, 64.4% were residents in Maringá, 24.9% lived in the 15th Region of Paraná and 8.7% lived out side the 15th Region of Paraná. The official Health System (SUS) was responsible for financing 73.8% of all admissions, private health insurances accounted for 14.9% and 11.3% of the patients were paying for their own hospital treatment. A difference was detected among the frequencies of the diagnoses according to financial support and city of residence. The average length of stay was 3,6 days and the hospital mortality rate was 2,7 deaths per hundred admissions.